![image](https://tex.z-dn.net/?f=+5x%5E%7B2%7D+-11x-5%3C7+x%5E%7B2%7D+%5C%5C%5C%5C-2x%5E2-11x-5%3C0%5C%5C%5C%5C2x%5E2%2B11x%2B5%3E0%5C%5C%5C%5CD%3D11%5E2-4%5Ccdot2%5Ccdot5%3D81%5C%5C%5C%5Cx_1%3D+%5Cdfrac%7B-11%2B9%7D%7B4%7D+%3D+-%5Cdfrac%7B1%7D%7B2%7D+%3B%5Cquad+x_2%3D-5%5C%5C%5C%5C2%28x%2B+%5Cfrac%7B1%7D%7B2%7D+%29%28x%2B5%29%3E0%5C%5Cx%5Cin%28-%5Cinfty%2C-5%29%5Ccup%28-%5Cdfrac%7B1%7D%7B2%7D%2C%2B%5Cinfty%29)
0\\\\D=11^2-4\cdot2\cdot5=81\\\\x_1= \dfrac{-11+9}{4} = -\dfrac{1}{2} ;\quad x_2=-5\\\\2(x+ \frac{1}{2} )(x+5)>0\\x\in(-\infty,-5)\cup(-\dfrac{1}{2},+\infty)" alt=" 5x^{2} -11x-5<7 x^{2} \\\\-2x^2-11x-5<0\\\\2x^2+11x+5>0\\\\D=11^2-4\cdot2\cdot5=81\\\\x_1= \dfrac{-11+9}{4} = -\dfrac{1}{2} ;\quad x_2=-5\\\\2(x+ \frac{1}{2} )(x+5)>0\\x\in(-\infty,-5)\cup(-\dfrac{1}{2},+\infty)" align="absmiddle" class="latex-formula">